(untitled) (Journal of Economic Research & Business Administration, 2015)
Systematic modernization of education, science and business must become a major factor in the way of innovation development of our society. To ensure the implementation of the strategic objectives of development, personnel training system in the country should become a dynamic, appropriately responding to the needs of industrial and innovational development